Received Signal Strength in a Macrocell in Lagos Environs Using Finite Element Method - O, Shoewu; N.T, Makanjuola; L.A, Akinyemi; A.O, Ogunlewe (Review of Computer Engineering Research, 2015)
This paper presents an analysis of received signal strength in a macrocell in Lagos environment using Finite Element Method (FEM). In this paper, six different site locations were covered and subdivided into peri-urban, open suburban, dense urban, open urban, suburban and exurban areas. It was deduced that the experimental values obtained was favourably with the FEM predicted values with the mean prediction error ranging between 6.66dB to 12.89dB while that of standard deviation error is 2.99dB to 8.09dB.